The experiences of lecturers in African, Asian and European universities in preparing and delivering blended health research methods courses: a qualitative study - Myroslava Protsiv; Salla Atkins (Taylor & Francis Group, 2016)
Background: Growing demand for Global Health (GH) training and the internationalisation of education requires innovative approaches to training. Blended learning (BL, a form of e-learning combining face-to-face or real-time interaction with computer-assisted learning) is a promising approach for increasing GH research capacity in low- to middle-income countries. Implementing BL, however, requires additional skills and efforts from lecturers. This paper explores lecturers' views and experiences of delivering BL courses within the context of two north-south collaborative research capacity building projects, ARCADE HSSR and ARCADE RSDH. Design: We used a qualitative approach to explore the experiences and perceptions of 11 lecturers involved in designing and delivering BL courses collaboratively across university campuses in four countries (South Africa, Uganda, India and Sweden). Data were collected using interviews in person or via Skype. Inductive qualitative content analysis was used. Results: Participants reported that they felt BL increased access to learning opportunities and made training more flexible and convenient for adult learners, which were major motivations to engage in BL. However, despite eagerness to implement and experiment with BL courses, they lacked capacity and support, and found the task time consuming. They needed to make compromises between course objectives and available technological tools, in the context of poor Internet infrastructure. Conclusions: BL courses have the potential to build bridges between low- and middle-income contexts and between lecturers and students to meet the demand for GH training. Lecturers were very motivated to try these approaches but encountered obstacles in implementing BL courses. Considerable investments are needed to implement BL and support lecturers in delivering courses.